Defining the "Ice Shed" of the Arctic Ocean's Last Ice Area and Its Future Evolution. Issue 9 (27th September 2021) - Newton, Robert; Pfirman, Stephanie; Tremblay, L. Bruno; DeRepentigny, Patricia
Abstract: Sea ice will persist longer in the Last Ice Area (LIA), north of Canada and Greenland, than elsewhere in the Arctic. We combine earth system model ensembles with a sea‐ice tracking utility (SITU) to explore sources of sea ice (the "ice shed") to the LIA under two scenarios: continued high warming (HW) rates and low warming (LW) rates (mean global warming below ca. 2°C) through the 21st century. Until mid‐century, the two scenarios yield similar results: the primary ice source shifts from the Russian continental shelves to the central Arctic, mobility increases, and mean ice age in the LIA drops from about 7 years to less than one. After about 2050, sea ice stabilizes in the LW scenario, but continues to decline in the HW scenario until LIA sea ice is nearly entirely seasonal and locally formed. Sea ice pathways through the ice shed determine LIA ice conditions and transport of material, including biota, sediments, and pollutants (spilled oil and industrial or agricultural contaminants have been identified as potential hazards). This study demonstrates that global warming has a dramatic impact on the sources, pathways and ages of ice entering the LIA. Therefore, we suggest that maintaining ice quality and preserving ice‐obligate ecologies in the LIA, including the Tuvaijuittuq Marine Protected Area north of Nunavut, Canada, will require international governance. The SITU system used in this study is publicly available as an online utility to support researchers, policy analysts, and educators interested in past and future sea ice sources and trajectories. Key Points: By mid‐century, the major source of sea ice to the Arctic's Last Ice Area (LIA) will shift from the Russian shelves, to the central Arctic If global mean warming stabilizes at 2C, the LIA should stabilize, with younger ages and different sources than in recent history If current warming rates continue, LIA ice will likely be local and seasonal, devastating ice‐obligate ecologies in this century